Prioritization and Evaluation of Flooding Tolerance Genes in Soybean [Glycine max (L.) Merr.] - Lai, Mu-Chien; Lai, Zheng-Yuan; Jhan, Li-Hsin; Lai, Ya-Syuan; Kao, Chung-Feng (Frontiers in Genetics, 2021)
Soybean [Glycine max (L.) Merr.] is one of the most important legume crops abundant in edible protein and oil in the world. Due to the drastic climate change, flooding, drought and unevenly distributed rainfall have gradually increased in terms of the frequency and intensity worldwide. In particular, severe flooding has caused extensive losses to soybean production. In light of the harsh situation, there has been an urge to breed strong soybean seeds with high flooding tolerance. The present study demonstrates bioinformatics big data mining and integration, meta-analysis, gene mapping, gene prioritization and systems biology for identifying prioritized genes of flooding tolerance in soybean. A total of 83 flooding tolerance genes (FTgenes), according to the appropriate cut-off point, were prioritized from 36,705 test genes that collected from multidimensional genomic features linking to soybean flooding tolerance. Several validation results using independent samples from SoyNet, GWAS, SoyBase, GO database and transcriptome databases all exhibited excellent agreement, suggesting these 83 FTgenes were significantly superior than others. Our results provide valuable information and contribution to varieties selection of soybean.